Lifestyle Related Chronic Kidney Disease Among Young Adults of Productive Age In Indonesia: Analysis of The 2023 Indonesian Health Survey - Akmal Fauzi; Yunita Dyah Puspita Santik; Arulita Ika Fibriana; Anwar Muttaqien (Borneo Scientific Publishing, 2026)
Chronic Kidney Disease (CKD) has traditionally been associated with older adults; however, its prevalence among adolescents and young adults has increased in recent years, largely due to changing lifestyle patterns. This trend threatens the productivity of the younger generation and may increase the burden on Indonesia’s healthcare system. This study aimed to analyze lifestyle-related factors associated with CKD among Indonesian young adult males aged 15–24 years. A quantitative cross-sectional study was conducted using secondary data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI). Total sampling was applied to eligible respondents, resulting in 46,510 male participants after excluding female respondents to minimize sex-related confounding. Data were analyzed using Chi-square tests and multivariable logistic regression. The results showed that the consumption of sugar-sweetened beverages (p < 0.001) and hypertension status (p = 0.001) were significantly associated with CKD. Multivariable analysis revealed that hypertension was the strongest factor associated with CKD among young adults, while the consumption of sugar-sweetened beverages also remained significantly associated with the condition. These findings highlight the importance of early prevention strategies focusing on blood pressure control and healthier dietary behaviors to reduce the risk of CKD in young populations. However, because of the cross-sectional design, the study can only identify associations and cannot establish causal relationships between lifestyle factors and CKD.